Altering polythiophene derivative substrates to control the electrodeposition morphology of Au particles toward ultrafine nanoparticles. Issue 80 (20th September 2019) - Fan, Yanchen; Liu, Shitai; Xiao, Jiewen; Wang, Tianshuai; Liu, Xiaopeng; Chen, Hetian; Gong, Yongji; Zhang, Qianfan
Abstract : A novel strategy for controlling the morphology of AuNPs by altering polythiophene derivative substrates was developed, and the nucleation mechanism of AuNPs on PTs was further explored theoretically. Abstract : A novel strategy for controlling the morphology of AuNPs by altering polythiophene derivative substrates was developed, and the nucleation mechanism of AuNPs on PTs was further explored theoretically. It is found that PTs with longer side chains can induce the electrodeposition of AuNPs with different morphologies and smaller particle sizes.